Penghambat Siklooksigenase-2: Obat Analgesik Anti-inflamasi Nonsteroid (Ains) Masa Depan - Kusumawati, Wiwik (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2002)
Nonsteroidal anti-inflammatory drugs (NSAIDs) exert its action through inhibition of prostaglandin (PG) synthesis. These drugs act by inhibition of cyclooxygenase (COX) which involved in PG synthesis. COX-lwhich is involv in PG synthesis may maintains normal gastric mucosa and influences kidney function. COX-2 a COX-1 homolog which is induced by inflammatory stimulan is inhibited by NSAIDs. The anti-inflammatory actions of NSAIDs are due to the inhibition of COX-2, whereas the unwanted side effects such as irritation of the stomach lining and toxic effect on the kidney are due to inhibition of the COX-1. In the treatment of inflammatory diseases such as osteoarthritis, using NSAIDs with selective COX-2 inhibition show effective benefit with minimal gastrointestinal side effect.Obat analgesik anti-inflamasi nonsteroid (AINS) bekerja menghambat enzim cyclooxygenase (COX) sehingga sintesis prostaglandin (PG) juga terhambat. COX- 1 yang terlibat dalam sintesis PG dapat mempengaruhi fungsi ginjal dan pertahanan mukosa lambung, sehingga hambatan pada COX-1 oleh obat AINS dapa: menyebabkan timbulnya efek samping pada lambung dan ginjal. COX-2 suatu hoÂ¬molog COX-1 terinduksi pada keadaan inflamasi dapat dihambat oleh obat AINS. Oleh karena itu obat AINS yang selektif menghambat COX-2 akan lebih menguntungkan terapi penyakit inflamasi seperti osteoartritis karena efek samping pada saluran cerna dan ginjal dapat dicegah.